2003
DOI: 10.1111/j.1550-7408.2003.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunocompetent Infants as a Human Reservoir for Pneumocystis jirovecii: Rapid Screening by Non‐Invasive Sampling and Real‐Time PCR at the Mitochondria1 Large Subunit rRNA Gene

Abstract: We tested a real-time PCR assay targeting the Pneumocystis jirovecii mitochondrial large subunit rRNA gene on 240 archival nasopharyngeal aspirates from non-immunosuppressed infants. The sensitivity of this assay appeared close to that of a conventional nested-PCR assay targeting the same locus. Because of its one-step procedure, and its sensitivity and rapidity, the real-time PCR assay is particularly suitable for screening individuals parasitized by P. jirovecii within large populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…Despite this wealth of knowledge, the current multilocus genotyping strategies have left many questions regarding transmission of P. jirovecii unanswered. For example, while it is clear that infants and immunocompetent adults are environmental reservoirs for P. jirovecii (83)(84)(85)(86)(87), there is not yet molecular evidence that these reservoirs are an important source of disease-causing P. jirovecii transmission to immunocompromised individuals. Because there is compelling evidence that transiently colonized immunocompetent mice can transmit P. jirovecii to immunosuppressed mice and vice versa (88,89), studies of P. jirovecii transmission among immunocompetent and immunosuppressed humans may help uncover a mechanism for disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Despite this wealth of knowledge, the current multilocus genotyping strategies have left many questions regarding transmission of P. jirovecii unanswered. For example, while it is clear that infants and immunocompetent adults are environmental reservoirs for P. jirovecii (83)(84)(85)(86)(87), there is not yet molecular evidence that these reservoirs are an important source of disease-causing P. jirovecii transmission to immunocompromised individuals. Because there is compelling evidence that transiently colonized immunocompetent mice can transmit P. jirovecii to immunosuppressed mice and vice versa (88,89), studies of P. jirovecii transmission among immunocompetent and immunosuppressed humans may help uncover a mechanism for disease prevention.…”
Section: Discussionmentioning
confidence: 99%
“…These patients had been hospitalized in two French university hospitals (hospitals A and B) between January 2008 and January 2012 for investigation of pulmonary symptoms (abnormal chest X-ray findings or cough) or fever. P. jirovecii was detected in BAL fluid samples by microscopic examination with methanol-Giemsa staining and an immunofluorescence assay (Monofluokit Pneumocystis; Bio-Rad, Marnes-La-Coquette, France) and/or a qualitative PCR assay targeting the mitochondrial large subunit (mtLSU) rRNA gene, as described previously (27). This assay was performed on an Applied Biosystems 7300 real-time PCR system using a plus/minus assay, which determined whether or not a specific target sequence was present.…”
Section: Methodsmentioning
confidence: 99%
“…In another study of 60 children of HIV-infected mothers, 3.5% were Pneumocystis colonized, and those with colonization had upper respiratory symptoms (275). Other investigators have documented colonization in immunocompetent pediatric populations with either acute respiratory syndromes or chronic lung diseases (142,170,290). Although one study found a high proportion of colonization in infants dying from sudden infant death syndrome, this association has not been supported by subsequent studies (14,298,300).…”
Section: Colonization In Animalsmentioning
confidence: 96%